2020
DOI: 10.3389/fmicb.2020.01517
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-MS-Based Metabolomics Analysis Reveals the Process of Schistosomiasis in Mice

Abstract: Metabolomics, as an emerging technology, has been demonstrated to be a very powerful tool in the study of the host metabolic responses to infections by parasites. Schistosomiasis is a parasitic infection caused by schistosoma worm via the direct contact with the water containing cercaria, among which Schistosoma japonicum ( S. japonicum ) is endemic in Asia. In order to characterize the schistosome-induced changes in the host metabolism and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Although the pathogenesis of IBD remains to be further explored, most studies believe that IBD is related to immune imbalance ( Nanini et al, 2018 ; Neurath, 2019 ; Mitsialis et al, 2020 ). As a common chronic parasitic worm ( Huang et al, 2016a ; Huang et al, 2016b ; Deol et al, 2019 ), a schistosome develops a variety of mechanisms to manipulate the adaptive immune system of the host while infecting the host ( Huang et al, 2016a ; Huang et al, 2019 ; Huang et al, 2020a ; Huang et al, 2020b ; Buck et al, 2020 ; Zheng et al, 2020 ). Studies have shown that the host immune system gradually shifts from its own invasive T helper 1 (Th1) cell response to anti-inflammatory Th2 cell response 4–6 weeks after cercariae penetrated the skin of the host ( Dunne and Cooke, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of IBD remains to be further explored, most studies believe that IBD is related to immune imbalance ( Nanini et al, 2018 ; Neurath, 2019 ; Mitsialis et al, 2020 ). As a common chronic parasitic worm ( Huang et al, 2016a ; Huang et al, 2016b ; Deol et al, 2019 ), a schistosome develops a variety of mechanisms to manipulate the adaptive immune system of the host while infecting the host ( Huang et al, 2016a ; Huang et al, 2019 ; Huang et al, 2020a ; Huang et al, 2020b ; Buck et al, 2020 ; Zheng et al, 2020 ). Studies have shown that the host immune system gradually shifts from its own invasive T helper 1 (Th1) cell response to anti-inflammatory Th2 cell response 4–6 weeks after cercariae penetrated the skin of the host ( Dunne and Cooke, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis of Schistosoma infection occurs from immunologic reaction of host body to parasite’s eggs, which detection of the disease prior to egg production apparently protect patients from the disease ( McManus et al., 2018 ). In the past few decades, many types of biomolecules have been identified as potential markers, for example, DNA ( Aula et al., 2021 ), proteins ( Zhou et al., 2010 ; Grenfell et al., 2013 ), and metabolites ( Li et al., 2011 ; Huang et al., 2020 ). To date, several attempts have been made to identify metabolite biomarkers at the early stage of schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Their data identified phenyl acetyl glycine in urine and 5-aminovalerate in feces as potential markers of infection. Currently, the study by Huang et al (2020) is the only published report to detect S. japonicum infection as early as 1 week postinfection, which is 3 weeks faster than standard methods. This study found 17 serum metabolites from mice that correlated with progression of schistosomiasis, including diphenol glucuronide and glycerol tribenzoate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry (MS)-based analysis platform makes it possible to identify and quantify small-molecule metabolites from different tissue or body fluid samples, which possibly reflect the health or disease status and provide clues for disease diagnosis and treatment ( Shah et al., 2015 ). For parasite infection, metabolomics analysis has been mostly applied for the discovery of biomarkers and the identification of a new drug target or intervention strategies ( Legido-Quigley, 2010 ; Li et al., 2016 ; Huang et al., 2020 ). However, only very few studies focused on the identification of anti-inflammatory molecules during parasite infection.…”
Section: Introductionmentioning
confidence: 99%